2013
DOI: 10.1532/hsf98.20121124
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making and Results of Coronary Artery Bypass Grafting for Patients with Poor Left Ventricular Function

Abstract: Coronary artery bypass grafting can be safely performed in patients with low ejection fraction with minimal postoperative morbidity and mortality. The viable myocardium could be reliably determined by positron emission tomography. Low ejection fraction patients could greatly benefit from coronary bypass surgery regarding postoperative ejection fraction, increased long-term survival, improvement in New York Heart Association classification, and higher quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies have shown that CABG confers a survival benefit over medical therapy in multiple subsets of patients, including those with left main CAD (Figure 6), 9-12 triple-vessel CAD, 13 and ischemic cardiomyopathy. 1,3-7,31-33 Many of these studies were conducted before the widespread use of antiplatelet and statin therapies and before the broad recognition of benefit from beta-blockers and ACE inhibitors/ARBs. There are no RCTs that have demonstrated a survival advantage of PCI over medical therapy in patients with SIHD.…”
Section: Revascularization In Sihdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CABG confers a survival benefit over medical therapy in multiple subsets of patients, including those with left main CAD (Figure 6), 9-12 triple-vessel CAD, 13 and ischemic cardiomyopathy. 1,3-7,31-33 Many of these studies were conducted before the widespread use of antiplatelet and statin therapies and before the broad recognition of benefit from beta-blockers and ACE inhibitors/ARBs. There are no RCTs that have demonstrated a survival advantage of PCI over medical therapy in patients with SIHD.…”
Section: Revascularization In Sihdmentioning
confidence: 99%
“…Several registry studies have supported these findings. 4-7,31-33 The use of PCI in this patient population requires more study.…”
Section: Revascularization In Sihdmentioning
confidence: 99%
“…36 Studies have shown that CABG confers a survival benefit over medical therapy in multiple subsets of patients, including left main CAD (Figure 3), [36][37][38][39] triple vessel CAD, 40 and ischemic cardiomyopathy. [41][42][43][44][45][46][47][48][49]…”
Section: B-rmentioning
confidence: 99%
“…1,2 Studies have demonstrated that revascularisation in the form of coronary artery bypass graft (CABG) confers survival benefit over medical treatment in patients with left main disease, triple-vessel disease (TVD) and ischaemic cardiomyopathy. [3][4][5][6][7][8][9][10][11][12][13] However, for patients with prohibitive operative risk or those with a personal preference…”
mentioning
confidence: 99%